Protective Immunity and New Vaccines for Lyme Disease. (17th October 2019) - Gomes-Solecki, Maria; Arnaboldi, Paul M; Backenson, P Bryon; Benach, Jorge L; Cooper, Christopher L; Dattwyler, Raymond J; Diuk-Wasser, Maria; Fikrig, Erol; Hovius, J W; Laegreid, Will; Lundberg, Urban; Marconi, Richard T; et al.
Abstract: Lyme disease, caused by some Borrelia burgdorferi sensu lato, is the most common tick-borne illness in the Northern Hemisphere and the number of cases, and geographic spread, continue to grow. Previously identified B. burgdorferi proteins, lipid immunogens, and live mutants lead the design of canonical vaccines aimed at disrupting infection in the host. Discovery of the mechanism of action of the first vaccine catalyzed the development of new strategies to control Lyme disease that bypassed direct vaccination of the human host. Thus, novel prevention concepts center on proteins produced by B. burgdorferi during tick transit and on tick proteins that mediate feeding and pathogen transmission. A burgeoning area of research is tick immunity as it can unlock mechanistic pathways that could be targeted for disruption. Studies that shed light on the mammalian immune pathways engaged during tick-transmitted B. burgdorferi infection would further development of vaccination strategies against Lyme disease. Abstract : A vaccine to protect against Lyme disease is needed and feasible. Different types of vaccines can target the bacteria and the tick vector pathogen-transport apparatus for human, animal, and ecological applications.